2017
DOI: 10.1111/1750-3841.13790
|View full text |Cite
|
Sign up to set email alerts
|

Bactericidal Efficacy of Hydrogen Peroxide‐Based Disinfectants Against Gram‐Positive and Gram‐Negative Bacteria on Stainless Steel Surfaces

Abstract: The study of the bactericidal properties of environmentally nontoxic disinfectants such as hydrogen peroxide, sole or in formulations with other disinfectants against Gram-positive and Gram-negative bacteria can enhance the efficacy of various commonly used disinfectant formulations with the hygiene benefits that it entails. Also, the use of hydrogen peroxide formulations can reduce the concentration levels of products that generate environmental residues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 64 publications
(45 citation statements)
references
References 29 publications
3
39
0
3
Order By: Relevance
“…The size of the material used was 4.0 × 4.0 cm 2 , while the stainless steel surfaces consisted of discs with a diameter of 2.0 cm and a thickness of 1.2 mm. Prior to performing the study, the surfaces were cleaned, disinfected and autoclaved at 121°C for 15 min (Ríos‐Castillo, González‐Rivas, & Rodríguez‐Jerez, ), except the antibacterial plastic, which was only cleaned with 70% isopropyl alcohol (2‐propanol) before use so as not to interfere with its antibacterial properties.…”
Section: Methodsmentioning
confidence: 99%
“…The size of the material used was 4.0 × 4.0 cm 2 , while the stainless steel surfaces consisted of discs with a diameter of 2.0 cm and a thickness of 1.2 mm. Prior to performing the study, the surfaces were cleaned, disinfected and autoclaved at 121°C for 15 min (Ríos‐Castillo, González‐Rivas, & Rodríguez‐Jerez, ), except the antibacterial plastic, which was only cleaned with 70% isopropyl alcohol (2‐propanol) before use so as not to interfere with its antibacterial properties.…”
Section: Methodsmentioning
confidence: 99%
“…When the solution with just hydrogen peroxide was applied on E. coli, P. aeruginosa, and S. Typhimurium biofilms, bubble formations were detected, and it was considered as a positive reaction to the presence of biofilms. The election of hydrogen peroxide as an indicator of the presence of biofilms in this study was justified by the positive activity of this compound in different types of bacteria commonly found in food-processing environments reported by Elkins, Hassett, Stewart, Schweizer, and MCDermott (1999) ;Christensen, Trønnes, Vollan, Smidsrød, and Bakke (1990);and Ríos-Castillo et al (2017). When the solution of hydrogen peroxide that contained crystal violet stain was applied to the surfaces (Figure 3), the biofilm area stained blue and an intense bubble formation was observed, indicating that biofilms are more visual when colorants are included in the formula.…”
Section: Detection Of Biofilms Using Dem and The Different Biodetectomentioning
confidence: 82%
“…This efficacy was attributed to differences in the structure of the cell walls between Gram-negative and Gram-positive bacteria [60]. Other studies support this theory, noting that S. aureus tends to be more resistant to adverse conditions and to many types of disinfectants than Gram-negative bacteria [61][62][63]. Additionally, it has been suggested that the cell membrane structure is more complex in Gram-negative bacteria, making it more susceptible to environmental changes [64].…”
Section: Antimicrobial Activity Of Ag-nps Zno-nps and Ag-zno-nps On mentioning
confidence: 99%